2014
DOI: 10.1016/j.jtbi.2014.02.027
|View full text |Cite
|
Sign up to set email alerts
|

The formation of tight tumor clusters affects the efficacy of cell cycle inhibitors: A hybrid model study

Abstract: Cyclin-dependent kinases (CDKs) are vital in regulating cell cycle progression, and, thus, in highly proliferating tumor cells CDK inhibitors are gaining interest as potential anticancer agents. Clonogenic assay experiments are frequently used to determine drug efficacy against the survival and proliferation of cancer cells. While the anticancer mechanisms of drugs are usually described at the intracellular single-cell level, the experimental measurements are sampled from the entire cancer cell population. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 88 publications
(123 reference statements)
0
25
0
Order By: Relevance
“…However, these conditions are not sufficient to explain the invasion of the local environment by malignant cells. Local invasion can arise by variations in the sensibility of hypoxia switch within the cellular population (or by similar mechanisms [39] fruit of a highly heterogeneous population). Pseudopalisade formation follows palisade formation, that follows invasion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, these conditions are not sufficient to explain the invasion of the local environment by malignant cells. Local invasion can arise by variations in the sensibility of hypoxia switch within the cellular population (or by similar mechanisms [39] fruit of a highly heterogeneous population). Pseudopalisade formation follows palisade formation, that follows invasion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Kim et al [41] used an off-lattice agent-based model to investigate combined therapies with cell-cycle checkpoint inhibitors. The authors considered cyclin-dependent kinases (CDKs), which are crucial in the regulation of cell-cycle progression and so represent attractive targets in anti-cancer therapy.…”
Section: Mathematical Models Of Tumour Multicellular Spheroidsmentioning
confidence: 99%
“…These results suggested that acute increase in tumor hypoxia can improve clinical efficacy of HAPs in pancreatic adenocarcinomas and other tumors. Moreover, we developed a mathematical model incorporating G1/S and G2/M cell-cycle checkpoints (39) to test the effectiveness of cyclin-dependent kinase (CDK) inhibitors on tumor growth-arrest. This in-silico study suggested that when tight tumor cell clusters are exposed to the CDK inhibitors, their growth suppression could be an effect of contact inhibition rather than of the drug mechanism, which may be important in designing the administration schedules and order of inhibitors acting at the G1/S and G2/M cell-cycle checkpoints.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%